PENGARUH REPUTASI KANTOR AKUNTAN PUBLIK TERHADAP PEMILIHAN KANTOR AKUNTAN PUBLIK OLEH PERUSAHAAN DI KOTA BATAM - Vargo Christian L. Tobing (LPPM Universitas Putera Batam, 2018)
This study aims to determine the effect of KAP's reputation on the selection of Public Accounting Firm. The sample in this research is 161 companies that use KAP services. This research uses descriptive quantitative method. The research results obtained is the reputation of KAP has a significant influence on the selection of KAP with a significant value of 0.001. R square value in this research is 25.2%, which means the influence of KAP's reputation against KAP election is 25.2% while the remaining 74.8% is influenced by other factors not included in this research model.